Students’ Perception and Utilization of Social Media for Enhancing Academic Library Services - Islam, Md. Maidul; Sultana, Shadia; Mostofa, Sk. Mamun (Universitas Pendidikan Ganesha, 2024)
The rapid proliferation of social media (SM) has revolutionized information sharing and communication, yet its potential in academic libraries remains underexplored. This study aims to investigate the usages and applications of social media platforms in the Dhaka University Library (DUL) to facilitate student engagement and resource access. The research adopts a quantitative approach, distributing 200 printed questionnaires to DUL students for data collection. A total of 177 usable responses were analyzed, yielding an 88.5% response rate. Data were processed using IBM SPSS to derive insights. Findings reveal that most users actively share information through platforms such as Facebook, Google+, Twitter, LinkedIn, and Academia. While students acknowledge the benefits of SM in enhancing library services, there is limited awareness of its potential drawbacks. Recommendations were developed for students and library authorities to optimize SM usage, focusing on fostering sustainable research development and distance learning. The study highlights implications for policymakers, social media developers, and educators in promoting ethical and meaningful online interactions. These findings underscore the transformative role of SM in academic libraries and its potential to enrich the learning experience in a digital age.